Oligodendrocyte myelin glycoprotein impairs dendritic arbors via schizophrenia risk gene Trio - Euan Parnell; Jessica M. Christiansen; Michelle A. Spratt; Shelby Ruiz; Matthew L. Macdonald; Peter Penzes; Robert A. Sweet; Melanie J. Grubisha (Neurobiology of Disease)
During adolescence, a critical developmental epoch coincident with the emergence of clinical symptoms of schizophrenia, cerebral cortical dendritic growth shifts from a rapid phase, reaching equilibrium. Oligodendrocyte Myelin Glycoprotein (OMGp) expression peaks during adolescence and has a known role in regulating dendritic stabilization. However, the precise signaling pathways transduced by OMGp are unknown. To identify these pathways, we performed unbiased phospho-proteomic analysis after OMGp stimulation, revealing 2991 phosphorylated proteins. Interestingly, several schizophrenia risk genes were identified as phospho-targets, including the potent risk factor Trio, which has a known role in regulating neurite outgrowth and the cytoskeleton through its dual Rac/RhoA catalytic domains. Phosphomimetic and phosphonull Trio9 constructs were employed to assess the functional role of OMGp-mediated phosphorylation at a novel phosphosite – Ser1258. Phosphomimetic Trio9 was deficient in Rac1 catalytic activity and induced loss of dendritic length and complexity compared to wild type protein. Moreover, phosphonull constructs blocked the OMGp-induced impairments in dendritic length and complexity. Together, these results highlight the ability of OMGp to regulate dendritic architecture by potently inhibiting the Rac1 catalytic activity of Trio through phosphorylation. These results provide a potential mechanism contributing to the emergence of neuronal structural dysfunction and schizophrenia symptomology during adolescence.